PERENCANAAN PRODUKTIVITAS KERJA DARI HASIL EVALUASI PRODUKTIVITAS DENGAN METODE FISHBONE DI PERUSAHAAN PERCETAKAN KEMASAN PT.X - Murnawan, Heri (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
Productivity is an important factor that affects the progress and setbacks of a company.Evaluation and planning is indispensable productivity after making measurements and it will bethe foundation to move on to the next cycle of the productivity improvements in the future. Amethod that can be used in the evaluation is a method Fishbone Diagram and continue planningwith Objective Matrix in accordance with the results of previous measurements. In the evaluationand planning, the selection of primary and secondary causes is an important step, because theselection can be used to determine the cause of the decline in productivity in the measurementperiod, the planning for the next period , and improved productivity for the company. The studytook place in Packaging Printing Company PT